2013
DOI: 10.6023/cjoc201208016
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Transition Metal-Catalyzed Aerobic Dehydrative Reactions of Alcohols and Amines and Related Researches

Abstract: In comparison with other methods, transition metal-catalyzed dehydrative N-alkylation of amines and amides with alcohols, commonly known as the borrowing hydrogen or hydrogen autotransfer reactions and the methodology, is a comparatively green and atom-economic method for the synthesis of the useful amine and amide derivatives. Recently, transition metal-catalyzed aerobic dehydrative N-alkylation method has also attracted much attention, for the reactions can be readily conducted under milder and simpler condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…

Am ild and atom-economic method was developed for direct and efficient synthesis of quinazolinones through at ransitionmetal-free aerobic oxidativec ascade annulation reaction of widely available o-aminoarylnitriles and alcohols. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among the methods reported, annulation reactions of o-aminoaryl acids and derivatives may be the most employed strategies, which include the condensation of o-aminoaryl acids with amides, nitriles, or acidd erivatives with an itrogen source (Scheme 1A), [2,3] the dehydrogenative or oxidative annulation of o-aminoarylamides with aldehydes, [4] masked aldehydes, [5] ketones, [6] imines, [7] or amines [8] (Scheme 1B), the carbonylative annulation of o-aminoarylamides with aC Os ource and aryl halides( Scheme 1C), [9] and the annulation of o-aminoarylnitriles with acid derivatives, [10] aldehydes, [11] or ketones [12] (Scheme 1D). Possibly owing to the "cesium effect", the water-soluble base CsOH was found to be crucial in all key steps of the reactionm echanism.B ecause a wide range of substrates can be used to prepare substituted quinazolinones withoutc ontamination by transition-metal residues, this method mayb eo fi nterestf or application in pharmaceutical synthesis.

…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…

Am ild and atom-economic method was developed for direct and efficient synthesis of quinazolinones through at ransitionmetal-free aerobic oxidativec ascade annulation reaction of widely available o-aminoarylnitriles and alcohols. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among the methods reported, annulation reactions of o-aminoaryl acids and derivatives may be the most employed strategies, which include the condensation of o-aminoaryl acids with amides, nitriles, or acidd erivatives with an itrogen source (Scheme 1A), [2,3] the dehydrogenative or oxidative annulation of o-aminoarylamides with aldehydes, [4] masked aldehydes, [5] ketones, [6] imines, [7] or amines [8] (Scheme 1B), the carbonylative annulation of o-aminoarylamides with aC Os ource and aryl halides( Scheme 1C), [9] and the annulation of o-aminoarylnitriles with acid derivatives, [10] aldehydes, [11] or ketones [12] (Scheme 1D). Possibly owing to the "cesium effect", the water-soluble base CsOH was found to be crucial in all key steps of the reactionm echanism.B ecause a wide range of substrates can be used to prepare substituted quinazolinones withoutc ontamination by transition-metal residues, this method mayb eo fi nterestf or application in pharmaceutical synthesis.

…”
mentioning
confidence: 99%
“…Possibly owing to the "cesium effect", the water-soluble base CsOH was found to be crucial in all key steps of the reactionm echanism.B ecause a wide range of substrates can be used to prepare substituted quinazolinones withoutc ontamination by transition-metal residues, this method mayb eo fi nterestf or application in pharmaceutical synthesis. [15] Therefore, the use of alcohols instead of the Scheme1.Generalmethods for quinazolinone skeleton construction.[a] Q. For example, the quinazolinone motif and derivatives are abundant in numerous synthetic compoundsa nd natural alkaloids with diverse biological and pharmacological activities such as antimalarial, antimicrobial, anti-inflammatory,a nticonvulsant, antihypertensive, anti-diabetic, anticancer,a ntitumor, cholinesteraseinhibitory, dihydrofolate reductase-inhibitory,a nd kinase-inhibitory properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] In contrast, we accidentally found that air played a crucial role in a Rhcatalyzed reaction, [12a] which subsequently led to the discovery of an air-promoted metal-catalyzed aerobic alkylation method and an interesting mechanism analogous to the relay race game. [12] We also proposed that metal-catalyzed aerobic alcohol oxidation should be a new way of alcohol activation/aldehyde generation, [12,14] which unfortunately it seems has not been generally recognized by the field so far. [3][4][5][6][7][8]12,14] During our further efforts to develop more preferable catalysts, we accidentally noticed that the reaction of alcohols and sulfonamides could be driven to completion by merely adding catalytic amounts of the intermediate aldehydes [Eq.…”
mentioning
confidence: 99%
“…[12] We also proposed that metal-catalyzed aerobic alcohol oxidation should be a new way of alcohol activation/aldehyde generation, [12,14] which unfortunately it seems has not been generally recognized by the field so far. [3][4][5][6][7][8]12,14] During our further efforts to develop more preferable catalysts, we accidentally noticed that the reaction of alcohols and sulfonamides could be driven to completion by merely adding catalytic amounts of the intermediate aldehydes [Eq. (2), R 2 = RSO 2 ], which implied that the lone aldehyde can catalyze the reaction efficiently to completion without any transition metal catalysts!…”
mentioning
confidence: 99%